Hadith Scholars Personality Development Review: Relevance in the development of psychological behavior - Zainal Badri, Khairul Nizam bin (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2021)
One of the definitions of personality involves character patterns that include feelings, thoughts and actions. Based on this definition it turns out that personality can not run away from the field of psychology. Personality traits are biological while personality values are environmental products influenced by culture, education and life. In the study of modern psychology, thought-based traits that are in the cognitive domain are higher than emotional traits in relation to values. In the tradition of Islamic science, there is a special traits, which is the yardstick of superior personality; that is, Al-â€˜Adalah or is called adilÂ (fairness). Related to the trait of adil is the trait of dhabit (strong memory). A qualitative study using this library approach seeks to trace the properties possessed by hadith scholars, who once inspired the West to apply those attributes in their intellectual work. Studies have found that these properties have unique characteristics because of their ability to integrate ontological, epistemological and axiological dimensions and also balance the role of cognitive and affective domains in human beings that direct human physiological and psychological behavior in a positive direction.